DEPRESSION IN FREDDIE MERCURYâ€™S SONG LYRICS: â€œBOHEMIAN RHAPSODYâ€, â€œSOMEBODY TO LOVEâ€ AND â€œLOVE OF MY LIFEâ€ - Risqullah, Zaki (Faculty of Letters, Dr. Soetomo University, 2018)
This research deals with Depression in Freddie Mercury?s song lyrics. It is focused on the symptoms of depression implied in the song lyrics entitled ?Bohemian Rhapsody?, ?Love of My Life?, and ?Somebody to Love?. The objectives of the study are to find out the poetic devices in Freddie Mercury?s song lyrics entitled ?Bohemian Rhapsody?, ?Love of My Life?, and ?Somebody to Love? and to describe the depression symptoms portrayed in Freddie Mercury?s song lyrics entitled ?Bohemian Rhapsody?, ?Love of My Life?, and ?Somebody to Love?. The theories used to analyse the data are Aaron T. Beck?s depression and William Wordsworth?s theory of poetry. Pragmatic approach and qualitative research design were applied in conducting the study. The techniques of data collection and analysis covered close reading and content analysis. Findings show that ?Bohemian Rhapsody? makes use of hyperbole, metonymy, situational irony, antithesis, repetition, and allusion as poetic devices. The depression symptoms undergone by the speaker of the song lyrics entitled ?Bohemian Rhapsody? cover Low Self-Evaluation., Loss of Emotional Attachments, and Negative Feelings toward Self. The second song lyrics entitled ?Someone to Love? employ repetition, hyperbole, and personification. The speaker of the song lyrics suffers from Reduction in Gratification. The song lyrics entitled ?Love of My Life? make use of hyperbole, repetition, personification, and symbol as the poetic devices. The character ?I?, in the song lyrics, suffer from Dejected Mood.